Efecto del entrenamiento neuromuscular en pacientes con neuropatía periférica inducida por quimioterapia. - Romero Calderón, María José (2025)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most frequent neurological complications in cancer patients, producing sensory, motor, and functional impairments that reduce autonomy and quality of life. Objective: This study aimed to identify the effects of neuromuscular training as a physiotherapeutic intervention in patients with chemotherapy-induced peripheral neuropathy, through a systematic review and analysis of recent scientific evidence. Methods: A systematic literature search was performed in international databases (PubMed, Cochrane Library, Scopus, ScienceDirect, and MEDLINE), using Boolean operators and keywords related to peripheral neuropathy, neuromuscular training, and physiotherapy in oncology. The selected articles were evaluated based on methodological quality and clinical relevance. Results: Findings revealed that neuromuscular training enhances muscle strength, balance, proprioception, and motor coordination, while decreasing neuropathic symptoms and improving functional performance. Additionally, complementary therapies—such as yoga, virtual reality, and electrical stimulation—may augment the therapeutic outcomes of physiotherapy interventions. Conclusion: Neuromuscular training is a safe and effective physiotherapeutic intervention for managing chemotherapy-induced peripheral neuropathy, promoting functional recovery and improving patients’ quality of life.